Traditionalist Muslims and Populism in Indonesia and Turkey - Martin van Bruinessen (Tashwirul Afkar, 2021)
In this article I follow some of the recent sociological literature on populism to bring out some important characteristics that distinguish it from other styles of politics and ideologies. Learning from the analysis on populism in Turkey as a comparative study, this article explores Indonesian Muslim populism phenomenon. Through tracing the experiences during the struggle for Independence and during the Old Order and the New Order, I do focus my study dealing with the question was the Anti-Ahok Mobilization of 2016-17 Populist? I argue it would be wrong to conclude that Islamic traditionalism, as represented by the NU (Nadhlatul Ulama), is systematically in conflict with Islamic populism. Instead of a struggle between traditionalist Islam and Islamic populism, therefore, I believe it is more correct to speak of populist forces within traditionalist Islam. There is populist opposition within NU and, even more threatening, there are populist traditionalist leaders outside the association who strongly appeal to the community of Nahdliyyin (NU followers).